2020
DOI: 10.1093/mnras/staa169
|View full text |Cite
|
Sign up to set email alerts
|

The accretion rates and mechanisms of Herbig Ae/Be stars

Abstract: This work presents a spectroscopic study of 163 Herbig Ae/Be stars. Amongst these, we present new data for 30 objects. Stellar parameters such as temperature, reddening, mass, luminosity and age are homogeneously determined. Mass accretion rates are determined from Hα emission line measurements. Our data is complemented with the X-Shooter sample from previous studies and we update results using Gaia DR2 parallaxes giving a total of 78 objects with homogeneously determined stellar parameters and mass accretion … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

23
126
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 92 publications
(150 citation statements)
references
References 70 publications
23
126
0
Order By: Relevance
“…In contrast, the L acc -L * trend followed by HAes when their accretion luminosities are inferred from MA is overplotted in green. This is equal within errorbars to the one followed by TTs and has a smaller slope ∼1 (see the bottom right panel of Figure 2 and [65,66] for details). [48] were used to infer the L acc values, as well as their data for M * and R * to derive the final MA-based values forṀ acc = L acc R * /GM * .…”
Section: Boundary Layer Measurements Of Haebe Starsmentioning
confidence: 64%
See 2 more Smart Citations
“…In contrast, the L acc -L * trend followed by HAes when their accretion luminosities are inferred from MA is overplotted in green. This is equal within errorbars to the one followed by TTs and has a smaller slope ∼1 (see the bottom right panel of Figure 2 and [65,66] for details). [48] were used to infer the L acc values, as well as their data for M * and R * to derive the final MA-based values forṀ acc = L acc R * /GM * .…”
Section: Boundary Layer Measurements Of Haebe Starsmentioning
confidence: 64%
“…The mismatch between MA and BL estimates is in last term due to differences between the underlying assumptions concerning energy transformation under both approaches (e.g., [66]). In MA the gravitational energy is carried through the accretion funnels and released at hot spots in the stellar surface, whereas in BL the kinetic energy of the rotating disk heats the BL when material is drastically decelerated in this region.…”
Section: Boundary Layer Measurements Of Haebe Starsmentioning
confidence: 99%
See 1 more Smart Citation
“…6, extinctions and effective temperatures are present in Vioque et al 2018 and references therein). Combining the Hα EWs of Vioque et al (2018) and Wichittanakom et al (2020) with the few sources present in IPHAS or VPHAS+ gave us r − Hα colour for 215 HAeBes. This is why neither r nor Hα passbands are combined with the rest in Sect.…”
Section: Herbig Ae/be Starsmentioning
confidence: 99%
“…Ababakr et al 2017), and spectro-photometric observations (e.g. Mendigutía et al 2011;Fairlamb et al 2015;Wichittanakom et al 2020) have shown that the lower mass Herbig Ae stars show accretion signatures consistent with T-Tauri stars, whereas Herbig Be stars appear to be inconsistent with magnetospheric accretion. A large caveat in these studies is that they do not include the less evolved sources in highmass PMS tracks (most Herbig Be stars observed to date are very close to the main sequence, Vioque et al 2018), which are obviously of paramount importance for understanding highmass accretion.…”
Section: Introductionmentioning
confidence: 99%